Keywords: care, maintenance, ste PERAWATAN DAN PEMELIHARAAN PADA TURBIN UAP DI PLTU REMBANG - ILHAM AKBAR ISLAMI (Department of Mechanical Engineering, University of Udayana, 2022)
Steam Power Plants (PLTU) currently have a strategic role in the electricity system in Indonesia. The maintenance system implemented by the steam power plant company will greatly affect the sustainability of the electricity produced. The steam power plant has several main parts in its production system, one of which is the turbine. The purpose of this research is to answer how to maintain the steam turbine at the Rembang Steam Power Plant (PLTU). The method used in this research is descriptive qualitative. Data collection was carried out through direct observation and interviews with related parties in the steam turbine maintenance section. The results show that care and maintenance on the steam turbine at the Rembang Steam Power Plant (PLTU) has proven to be effective and efficient to minimize various disturbances or problems that occur in the components of the steam turbine and can minimize maintenance costs and work safety can be guaranteed. Keywords: care, maintenance, steam turbine